Robust Control and Synchronization of 3-D Uncertain Fractional-Order Chaotic Systems with External Disturbances via Adding One Power Integrator Control. (22nd May 2019) - Luo, Runzi; Huang, Meichun; Su, Haipeng
Abstract : This paper investigates the control and synchronization of a class of 3-D uncertain fractional-order chaotic systems with external disturbances. The adding one power integrator control scheme, which is the generalization of the traditional backstepping method, is used to investigate the global stability of the control and synchronization manifold. As a result, several criteria for chaos control and synchronization are obtained. Compared with the previous results, the presented strategies can not only be applied to a class of strict-feedback systems but also be applied to more general class of fractional-order chaotic systems. In addition, the proposed controllers are robust against uncertain parameters and external disturbances. To validate the effectiveness of the proposed criteria, two illustrative examples are given.